Dying in long-term care facilities in Europe: the PACE epidemiological study of deceased residents in six countries - Elisabeth Honinx; Nanja van Dop; Tinne Smets; Luc Deliens; Nele Van Den Noortgate; Katherine Froggatt; Giovanni Gambassi; Marika Kylänen; Bregje Onwuteaka-Philipsen; Katarzyna Szczerbińska; Lieve Van den Block; on behalf of PACE (BMC, 2019)
Abstract Background By 2030, 30% of the European population will be aged 60 or over and those aged 80 and above will be the fastest growing cohort. An increasing number of people will die at an advanced age with multiple chronic diseases. In Europe at present, between 12 and 38% of the oldest people die in a long-term care facility. The lack of nationally representative empirical data, either demographic or clinical, about people who die in long-term care facilities makes appropriate policy responses more difficult. Additionally, there is a lack of comparable cross-country data; the opportunity to compare and contrast data internationally would allow for a better understanding of both common issues and country-specific challenges and could help generate hypotheses about different options regarding policy, health care organization and provision. The objectives of this study are to describe the demographic, facility stay and clinical characteristics of residents dying in long-term care facilities and the differences between countries. Methods Epidemiological study (2015) in a proportionally stratified random sample of 322 facilities in Belgium, Finland, Italy, the Netherlands, Poland and England. The final sample included 1384 deceased residents. The sampled facilities received a letter introducing the project and asking for voluntary participation. Facility manager, nursing staff member and treating physician completed structured questionnaires for all deaths in the preceding 3 months. Results Of 1384 residents the average age at death ranged from 81 (Poland) to 87 (Belgium, England) (p < 0.001) and length of stay from 6 months (Poland, Italy) to 2 years (Belgium) (p < 0.05); 47% (the Netherlands) to 74% (Italy) had more than two morbidities and 60% (England) to 83% (Finland) dementia, with a significant difference between countries (p < 0.001). Italy and Poland had the highest percentages with poor functional and cognitive status 1 month before death (BANS-S score of 21.8 and 21.9 respectively). Clinical complications occurred often during the final month (51.9% England, 66.4% Finland and Poland). Conclusions The population dying in long-term care facilities is complex, displaying multiple diseases with cognitive and functional impairment and high levels of dementia. We recommend future policy should include integration of high-quality palliative and dementia care.